More. Better. Integrated. - Ryan Gedney (Oz, 2011)
I would like to take a moment to appreciate the simplicity of discussions about technology that happened only a short time ago. What brand of parallel bar or type of pencil one used largely led the debate. Lead, ink, wood and other materials that made up this analog world were relatively easy to learn and use.